2017
DOI: 10.12783/dtetr/icamm2016/7371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Properties of Steel Fiber Reinforced Concrete Orthogonal Analysis

Abstract: Abstract. Through the research on the dynamic compressive strength of steel fiber reinforced concrete and comprehensive analysis of four factors: water-cement ratio, sand rate, steel fiber and steel fiber content types on kinetic properties of concrete, and further analysis of orthogonal test to find the optimal ratio of steel fiber reinforced concrete. Final conclusion: at low, medium and high strain rate, impact of SFRC dynamic compressive strength of primary and secondary factors are: sand ratio →steel fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…It is shown that the increase of fiber content will cause the strain rate to decrease, namely, the strain rate sensitivity will be higher with the fiber content is lower, which is consistent with Ref. [10].…”
Section: Verification Considering the Strain Rate Effectsupporting
confidence: 87%
“…It is shown that the increase of fiber content will cause the strain rate to decrease, namely, the strain rate sensitivity will be higher with the fiber content is lower, which is consistent with Ref. [10].…”
Section: Verification Considering the Strain Rate Effectsupporting
confidence: 87%